Comparison between Ocimum Sanctum Hepatoprotector Extract and Curcuma Xanthorrhiza on the Histological Structure of Aspartame-Induced Wistar Rats - Des Suryani; Humairah Medina Liza Lubis (Budapest International Research and Critics University, 2019)
The use of aspartame is still controversial, because there are studies stating that aspartame is safe to use, and there are studies suggesting aspartame has the potential to damage the liver, but aspartame has been approved by the FDA and BPOM in Indonesia with a daily dose of 50 mg / kg / day, the level of public knowledge we are still low to allow this dose to be overtaken, coupled with the presence of several food products that do not include the content of aspartame, basil leaves have been known to have hepatoprotector effect, but the dosage is still varied, and no researchers have compared curcuma Xanthoriza which is herbal medicine that has been quite well accepted in the community, Objective: to compare the hepatoprotector effect of basil leaf extract with xanthoriza curkuma, Method: Laboratory experimental study with posttest only with control group design. Wistar rats were divided into 5 groups and treated for 30 days. This study analyzed the histopathology of liver using paraffin histotechnics blocks, with HE staining and light microscopy. Analysis of degeneration degree using Kruskal-walis analysis post Hoc Mann-Whitney Results showed an increase in the degree of degeneration in the aspartame group at a dose of 100 mg / kgbb / day (p <0.05) compared to the normal group and treatment. Use of aspartame past the ADI dose damaged the liver, kurkuma and basil leaf extract at a dose of 300 mg / kg has the same protective effect on aspartame-induced rat liver, conclusions: aspartame is toxic for the liver, the use of basil leaf extract at a dose of 300 mg / kg / day or kurkuma xhantoriza extract can reduce the toxicity of aspartame.